Niestacjonarne pole temperatury w półprzestrzeni w przypadku ruchomego ogrzania na brzegu - T. Różnowski (Engineering Transactions, 1969)
In this paper the nonstationary distribution of temperature is considered in a semi-space one half of whose free surface was suddenly heated by a moving field of heat to a constant temperature, after which the heating moves with a constant velocity. Using 1 e technique of integral transformations and the method of solution according to the author's previous papers, the temperature in the semi-space is determined in the form of a function, from which the series representation results directly expressed by the formulae (22) and (23) in [1]. Some particular cases are investigated, and the possibility of utilizing the relationships obtained for solving problems with more complex boundary conditions are presented in [2] and [3].